2017
DOI: 10.1007/s11482-017-9528-5
|View full text |Cite
|
Sign up to set email alerts
|

Primary and Secondary Caregiver Reports of Quality of Life in Pediatric Asthma: Are they Comparable?

Abstract: Purpose This study aimed to compare primary and secondary caregiver QOL within families of children with asthma and determine the potential importance of including secondary caregiver QOL in clinical and research settings. Methods Participants included 118 families of children with asthma that had primary and secondary caregivers. Families completed measures in a single research session. Caregivers reported on QOL, psychological functioning, and family burden; children completed a measure of QOL. Child lung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Although we have to be careful drawing firm conclusions, also given the small sample size, this finding in itself could be clinically relevant, stressing the differences in time investment, perceptions, experiences, and perspectives of the caring situation between primary versus secondary caregivers that might give rise to problems in family functioning. Everhart et al (2018), for instance, found that differences in QoL scores between both caregivers in families of children with pediatric asthma were associated with more family burden and psychological problems in the primary caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…Although we have to be careful drawing firm conclusions, also given the small sample size, this finding in itself could be clinically relevant, stressing the differences in time investment, perceptions, experiences, and perspectives of the caring situation between primary versus secondary caregivers that might give rise to problems in family functioning. Everhart et al (2018), for instance, found that differences in QoL scores between both caregivers in families of children with pediatric asthma were associated with more family burden and psychological problems in the primary caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some research evidence suggests that parents of children with long-term illnesses and disabilities often face an increased risk of union dissolution compared to parents of children without such disabilities and that this continues into the child's adulthood (e.g., Hartley et al, 2010). As well, the few studies that have compared caregiving outcomes among primary and secondary caregivers report greater burden and stress among primary than secondary caregivers (Bédard et al, 2001;Everhart, Greenlee, Winter, & Fiese, 2018). Yet the presence of secondary caregivers as well as of other supportive resources including formal in-home and other care services may serve to reduce the burden and thus, stress experienced by primary caregivers (Verbakel, Metzelthin, & Kempen, 2018).…”
Section: Background In Theory and Researchmentioning
confidence: 99%
“…In addition, the results of the hypothesis test according to household incomes showed that the influence of maternal depression on fathers' marital conflict was found to be large in the group that earns less than the average income. The reason is that since asthma is a disease that requires repetitive and long-term treatment, and the financial burden of parents raising children with asthma is relatively greater than that of parents raising normal children [3], the level of depression of mothers in families of lower income is high due to financial burden related to the treatment process of children and it also influences fathers who are responsible for financial activities of the family. Accordingly, it is necessary for the government to prepare a financial support system for families raising asthmatic children.…”
Section: Discussionmentioning
confidence: 99%
“…Authors' information 1 Nursing Science, Jinju Health College, 51, Uibyeong-ro, Jinju-si, Gyongsangnam-do 2 Department of Nursing, Changwon National University, 20 Changwondaehak-ro, Uichang-gu, Changwon, Gyeongsangnam-do, Korea 3 College of Nursing Science, Kyung Hee University, 24 Kyungheedae-ro,…”
Section: Ethics Approval and Consent To Participatementioning
confidence: 99%
See 1 more Smart Citation